Dow Chemical Company Styrene plant - Dow Chemical Company (1952)
General view of an unidentified employee climbing stairs at the Dow Chemical Company's Styrene plant located in Freeport, Texas. An organic compound derived from benzene, styrene is a precursor to polystyrene and was popularized in the 1940's as a feedstock for synthetic rubber.
Keywords: Employees; Industries; Dow Chemical Company; Styrene industry; Monomers; Styrene